Aqueous cadmium removal by hydroxylapatite and fluoroapatite - Matusik, Jakub; Bajda, Tomasz; Manecki, Maciej (Geology, Geophysics and Environment, 2012)
Reducing the bioavailability of toxic heavy metals in groundwaters and urban soils by phosphate addition is an effective technique described in the literature. It is based on the reaction between metal ions and phosphates and results in the precipitation of metal substituted phosphate phases. The formed phosphates are highly insoluble and thermodynamically stable over almost entire pH and Eh range. In the presented study the efficiency and mechanism of cadmium uptake by synthetic hydroxylapatite and natural fluoroapatite was examined within the pH range of 3-7 for different reaction times (2—1440 hours). The solids after reactions were characterized by XRD and SEM-EDS. Percentage reduction of cadmium concentration in the experiments with fluoroapatite and hydroxylapatite, regardless of pH, did not exceed 17% and 25%, respectively. Cadmium uptake from the solution mainly resulted from the formation of cadmium phosphates and/or Ca-Cd phosphate solid solutions on the apatites surface. The release rate of phosphate ions by hydroxylapatite was relatively high. This promoted crystallization of a large number of small crystals. In turn dissolution of fluoroapatite was slower and thus the formation of large crystals was observed. There was no clear evidence for cadmium-calcium ion-exchange mechanism.